Indoor temperature, relative humidity and CO2 levels assessment in academic buildings with different heating, ventilation and air-conditioning systems. (April 2018) - Asif, Ayesha; Zeeshan, Muhammad; Jahanzaib, Muhammad
Abstract: Indoor air quality (IAQ) is a matter of immense concern for human health as people spend major portion of their lifetime indoor. Keeping in view, this study was aimed to investigate and compare the IAQ and thermal comfort in classrooms of four buildings of an educational institute having different types of heating ventilation and air conditioning system. On-site continuous measurements of indoor levels of CO2, temperature and relative humidity were recorded at an interval of 1 min for both weekdays, including occupational and non-occupational hours as well as weekends. Simultaneous outdoor temperature and relative humidity measurements were also used in the analysis. Statistical analysis of mean hourly values of each studied classroom showed significant difference (p < 0.05) in CO2 levels over the weekday and also among different buildings. Similarly, variation in hourly mean levels of thermal comfort parameters was also found significant (p < 0.05) among the buildings as well as over the weekday. However, variation in hourly mean temperature over weekday for one particular building and all three parameters over weekends for all buildings was not significant (p > 0.05). Exceedance in levels of CO2 from ASHRAE standards was found to be more in buildings with non-centralized systems as compared to buildings with centralized systems during the occupational period. Moreover, thermal comfort parameters were found to be influenced by outdoor climatic conditions and buildings orientation. Graphical abstract: Image 1 Highlights: T, RH and CO2 levels of buildings with different HVAC system are compared. Naturally ventilated classrooms exceeded safe CO2 level at higher frequency. T in classrooms was higher than recommended during most of the monitoring period. Outdoor climatic conditions were linked with indoor thermal comfort parameters.